2006
DOI: 10.1002/andp.200510189
|View full text |Cite
|
Sign up to set email alerts
|

Cosmologies from higher-order string corrections

Abstract: We study cosmologies based on low-energy effective string theory with higher-order string corrections to a tree-level action and with a modulus scalar field (dilaton or compactification modulus). In the presence of such corrections it is possible to construct nonsingular cosmological solutions in the context of Pre-BigBang and Ekpyrotic universes. We review the construction of nonsingular bouncing solutions and resulting density perturbations in Pre-Big-Bang and Ekpyrotic models. We also discuss the effect of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…This property comes from the fact that the GB term is a Lovelock scalar. Theories with the more general Lagrangian density R /2 + f ( R , P 1 , P 2 ) have been studied by many people in connection to the dark energy problem [142, 110, 521, 420, 585, 64, 166, 543, 180]. These theories are plagued by the appearance of spurious spin-2 ghosts, unless the Gauss-Bonnet (GB) combination is chosen as in the action (12.7) [465, 153, 447] (see also [110, 181, 109]).…”
Section: Gauss-bonnet Gravitymentioning
confidence: 99%
“…This property comes from the fact that the GB term is a Lovelock scalar. Theories with the more general Lagrangian density R /2 + f ( R , P 1 , P 2 ) have been studied by many people in connection to the dark energy problem [142, 110, 521, 420, 585, 64, 166, 543, 180]. These theories are plagued by the appearance of spurious spin-2 ghosts, unless the Gauss-Bonnet (GB) combination is chosen as in the action (12.7) [465, 153, 447] (see also [110, 181, 109]).…”
Section: Gauss-bonnet Gravitymentioning
confidence: 99%
“…This study also shows the instability of the exact solution found in [311], as the initial singularity is approached. The asymptotic behaviour of theories with quadratic corrections to the Einstein-Hilbert were studied, in the context of string cosmology, in [1090,236,1218]. Exponential and power-law FLRW solutions in higher-dimensional string inspired models are found in [855,856,17].…”
Section: Cosmological Solutionsmentioning
confidence: 99%
“…It is tempting to study the string curvature corrections to Einstein gravity amongst which the Gauss-Bonnet correction enjoys special status. A large number of papers are devoted to the cosmological implications of string curvature corrected gravity [2,3,4,5,6,7,8,9,10,11]. These models suffer from several problems.…”
Section: Introductionmentioning
confidence: 99%